Shepherding parents to prepare for end-of-life decision-making: a critical phenomenological study of the communication approach of paediatricians caring for children with life-limiting conditions in Australia - Katrina Williams; Lynn Gillam; Jenny Hynson; Sidharth Vemuri; Jenny O'Neill (BMJ Open)
Background/objectives Shared decision-making is widely accepted as the best approach for end-of-life decision-making for children with life-limiting conditions. Both paediatricians and parents find benefit in preparing for such decisions. However, little detail is known about this preparatory process. This study aims to explore how paediatricians prepare parents for end-of-life decision-making for a child with a life-limiting condition using clinical simulation.Design Individual, semistructured, post-simulation qualitative interviews of paediatricians and parent-actors.Setting Acute intensive and long-term outpatient paediatric care in Victoria, Australia.Participants 18 purposively sampled paediatricians who treat children with life-limiting conditions and the two parent-actors involved in all simulations. Paediatricians were excluded if they assisted in the study design, worked within specialist palliative care teams or did not provide clinical care outside the neonatal period.Results Three key themes in a preparatory process (termed ‘shepherding’) were identified: (1) paediatricians aim to lead parents along a pathway to future end-of-life decisions, (2) paediatricians prefer to control the pace of these discussions and (3) paediatricians recognise they need to have courage to face risk with this preparation. Paediatricians use a variety of shepherding strategies to influence the pace, content and framing of discussions, which may help prepare parents to make the best end-of-life treatment decisions when the time comes.Conclusions Shepherding is a newly identified, subtle process intended to influence parents by guiding their understanding of their child’s health and potential suffering in advance of decision-making. Shepherding does not fit within current descriptions of physicians’ decision-making influence. Paced reflection, thinking and provision of information are shepherding strategies preferred by paediatricians, and these appear the same regardless of whether paediatricians intend to steer parents towards particular treatment decisions or simply prepare them for the process of decision-making. Further study about the intention of this influence and parental perception of this communication is needed.